SUPER TEETH® - Farrah Dina , Y.; Lee, K.W.; Hoo, Y.M.; Yap, S.W. (University of Malaya, 2014)
This mobile app is designed to educate public especially small children age between 3 to 12 year old on how to take care of their teeth. It contains information on teeth diseases, how to brush properly, quiz and games etc. This trademark registered under class 9 and 41